Making interview transcripts real: the reader's response. (February 2015) - Butler, Clare
This research note considers how we interact with verbatim interview transcripts. Drawing on reader-response theory, the note examines the possible effect of readers' engagement with this often dysfluent talk-as-text. Lessons from the reader-response literature suggest that in realizing verbal transcripts we may be convincingly representing changed worlds to our audiences – specifically, our world and not their world. As a result of this potential hazard, this note alerts qualitative researchers to be mindful of the possible impact of engaging with talk-as-text and offers strategies to retain robustness in their research.